KAM - A KNOWLEDGE-BASED TOOL FOR DEVELOPING COMPUTER ALGEBRA SYSTEMS (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1998)
The paper presents a description of KAM - a knowledge-based tool for building computer algebra systems developed at the Faculty of Mathematics and Informatics, Sofia University. The main features of KAM are analyzed. The architecture of KAM and the knowledge representation formalisms supported by the tool transformation rules, frames, rewrite rules, generalized rules, are briefly described. A presentation of the experimental computer algebra system STRAMS being under development as an application of KAM is given.